Xanthoxyletin blocks the RANK/RANKL signaling pathway to suppress the growth of human pancreatic cancer cells - Zhang Xin; Li Luming; Wu Yan (Acta Pharmaceutica)
Xanthoxyletin is a vital plant-derived bioactive coumarin. It has been shown to exhibit anticancer effects against different human cancers. Nonetheless, the anticancer effects of xanthoxyletin against human pancreatic cancer cells have not been evaluated. Against this backdrop, the present study was designed to evaluate the anticancer effects of xanthoxyletin in human pancreatic cancer cells and to decipher the underlying molecular mechanisms. The results revealed a significant (p < 0.05) upregulation of receptor activator of NF-kappaB (RANK), receptor activator of NF-kappaB ligand (RANKL) and osteoprotegerin (OPG) in human pancreatic tissues and cell lines at both transcriptional and translational levels. The administration of pancreatic cancer cells with xanthoxyletin diminished the viability of Capan-2 cells in a concentration-dependent manner and led to a significant decline in RANK, RANKL, and OPG expression. Silencing of RANK and xanthoxyletin treatment declined the viability of Capan-2 pancreatic cancer cells via induction of apoptosis. However, pancreatic cancer cells overexpressing RANK could rescue the growth inhibitory effects. Collectively, xanthoxyletin targets the RANK/RANKL signaling pathway in pancreatic cancer cells to induce cell apoptosis and may prove to be an important lead molecule.